Pediatric trauma management in rural India - Avoid the time trap! - Sujatha Thyagarajan; Dinesh Chirla (Wolters Kluwer Medknow Publications, 2017)
Golden hour management of pediatric trauma is challenging in the rural settings in India. There are significant time traps due to absence of robust systems, lack of adequate transport, age appropriate equipment, trained personnel and inadequate stabilization at the first point of healthcare facility. There is a need to empower low resource areas to facilitate effective golden hour management of pediatric trauma in the right place at the right time.